PEMASARAN DAN UPAYA DALAM MEMPENGARUHI HARAPAN STAKEHOLDER DALAM LEMBAGA PENDIDIKAN ISLAM - Muhammad Mukhtar (Universitas Islam Nahdlatul Ulama Jepara, 2017)
Marketing is an activity or approach that always oriented on consumers whoaim to make management decisions. Marketing should be done with careful planning and clear goals and oriented to customer satisfaction. Marketing in educational institutions is to establish a good image (image) of the institution and attract a number of prospective students. Marketing should be oriented to